2010
DOI: 10.1002/j.2162-6057.2010.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Cultural Examination of Creative Problem Solving Style: The Dutch Translation of VIEW

Abstract: Creativity and Creative Problem Solving are globally important. This study examined the cross-cultural applicability of creative problem solving styles by translating VIEW: An Assessment of Problem Solving Style from its native English into Dutch and examining its psychometric properties and preliminary validation evidence. In general, support was found for the Dutch translation of VIEW in that it performed similarly to its original with regard to item performance on factor analysis, had acceptable levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…VIEW has demonstrated relationships to other variables such as learning and teaching styles (Doheny, Houtz & Selby, 2008;Selby, Shaw & Houtz, 2003), other measures of learning style, cognitive style, and personality type (Selby et al, 2007a;Sokolowska, 2006;Woodel-Johnson, 2010), coping styles (Maghan, 2008), and career interests (Crerar, 2010;Maghan & Houtz, 2009). VIEW has also demonstrated application potential in educational (Shaw, Selby & Houtz, 2009) business (Stead, 2008) and cross-cultural contexts (Isaksen, De Schryver & Onkelinx, 2010).…”
Section: Problem-solving Stylementioning
confidence: 99%
“…VIEW has demonstrated relationships to other variables such as learning and teaching styles (Doheny, Houtz & Selby, 2008;Selby, Shaw & Houtz, 2003), other measures of learning style, cognitive style, and personality type (Selby et al, 2007a;Sokolowska, 2006;Woodel-Johnson, 2010), coping styles (Maghan, 2008), and career interests (Crerar, 2010;Maghan & Houtz, 2009). VIEW has also demonstrated application potential in educational (Shaw, Selby & Houtz, 2009) business (Stead, 2008) and cross-cultural contexts (Isaksen, De Schryver & Onkelinx, 2010).…”
Section: Problem-solving Stylementioning
confidence: 99%
“…Research has also been undertaken into other more formal and structured facilitation techniques, for example a comparison of Appreciative Inquiry (AI) and Creative Problem Solving (CPS) undertaken with both Agrisgôp groups and groups of Agrisgôp Leaders (Owen, 2008). Twenty-four participants in four equal sized teams engaged in a day's facilitation of either AI (Lewis et al, 2008) or CPS (Isaksen et al, 2000) and team potency was measured by individual questionnaires at the beginning, at the half way point and at the end of the session. The results suggested that although there was no effect on potency at the mid-task stage, group potency was higher at the post-task stage in both AI and CPS interventions.…”
Section: Agrisgôp Action Learning and Other Group Facilitation Technmentioning
confidence: 99%